2016
DOI: 10.1080/2162402x.2015.1134073
|View full text |Cite
|
Sign up to set email alerts
|

Priming of neutrophils toward NETosis promotes tumor growth

Abstract: Neutrophils play a major role in cancer biology and both pro-and antitumoral functions of tumorinfiltrating neutrophils have been described. We have shown that tumors, by releasing G-CSF into the bloodstream, prime circulating neutrophils to form neutrophil extracellular traps (NETs) and we have detected the presence of NETs within the tumor microenvironment. Here, we report, using PAD4-deficient mice with a defect in neutrophil chromatin decondensation and NET formation, that the priming of neutrophils toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
181
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(193 citation statements)
references
References 38 publications
3
181
0
1
Order By: Relevance
“…Similarly, neutrophils from naïve mice treated with recombinant G‐CSF were predisposed to NET formation when stimulated with platelet activating factor ex vivo . Although this study mechanistically recognized NETs as driving a pro‐thrombotic state in the lungs of tumour‐bearing mice, the authors later demonstrated that NETs have a role in tumour growth . Interestingly, the latter study indicated that tumour‐derived levels of G‐CSF dictated the ability of tumour‐infiltrating neutrophils to form NETs, linking their formation to a specific neutrophil phenotype (CD11b high ) that was found in high‐G‐CSF‐secreting tumours .…”
Section: Neutrophil Extracellular Trapsmentioning
confidence: 87%
“…Similarly, neutrophils from naïve mice treated with recombinant G‐CSF were predisposed to NET formation when stimulated with platelet activating factor ex vivo . Although this study mechanistically recognized NETs as driving a pro‐thrombotic state in the lungs of tumour‐bearing mice, the authors later demonstrated that NETs have a role in tumour growth . Interestingly, the latter study indicated that tumour‐derived levels of G‐CSF dictated the ability of tumour‐infiltrating neutrophils to form NETs, linking their formation to a specific neutrophil phenotype (CD11b high ) that was found in high‐G‐CSF‐secreting tumours .…”
Section: Neutrophil Extracellular Trapsmentioning
confidence: 87%
“…Therefore, NE may be localized to several different compartments – intracellular (granular, and even nuclear) or extracellular, consistent with the staining seen in Fig 7 and Supplementary Fig 2. Cancer cells secrete factors that predispose granulocytes to undergo NETosis, leading to enhanced primary tumor growth, metastatic initiation and colonization, and cancer-associated morbidities like thrombosis and end organ damage (2123). Indeed, prostate cancer patients have elevated plasma concentrations of G-CSF and IL8, two factors that likely prime circulating and infiltrating granulocytic MDSCs for NETosis (24, 27).…”
Section: Discussionmentioning
confidence: 99%
“…NETs are externalized protease-laden DNA fibers released upon neutrophil activation in response to infection or cancer burden (20). NETs play an important role in cancer pathology, promoting primary tumor growth and development of a metastatic niche (2123). In the context of prostate cancer, tumor-derived cytokines like IL8 have been shown to attract myeloid-derived suppressor cells (MDSCs) and elicit extrusion of NETs within the tumor microenvironment (24).…”
Section: Introductionmentioning
confidence: 99%
“…This was related to their sheer numbers, as circulating pDC were 27 times more efficient in secreting IFN-α, but PMN were 100 times more frequent (289). Second, both T1-IFNs and IL-17-induced G-CSF prime PMN for NETosis (250, 290). In accord, circulating PMN of SLE patients are also the main cells expressing the transcriptional T1-IFN signature and release more NETs than PMN from healthy individuals (250, 253, 288, 289, 291, 292).…”
Section: T1-ifns the Th17 Response And Their Interactions In Autoimmmentioning
confidence: 99%